2022
DOI: 10.14740/jocmr4798
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Relationship Between Cognitive Function and Social Function in Patients With Schizophrenia

Abstract: Background: Social dysfunction is associated with decreased activity, employment difficulties, and poor prognosis in patients with schizophrenia. Cognitive functions, such as attention and processing speed, have been implicated in the social functions of schizophrenia patients; however, the relationship between cognitive functions and social functions remains unclear. Thus, understanding the factors that influence social functioning can aid the development of therapeutic strategies for schizophrenia. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Schizophrenia is a chronic psychotic condition affecting approximately 24,000,000 individuals worldwide and constitutes the majority of patients in psychiatric facilities of Egypt [13,14] . Social functioning is very impaired among schizophrenic patients and is repeatedly associated with poor adherence to medical treatment, poor prognosis, higher relapse rate, and increased risk of premature mortality [15,16] . A study conducted by Al-Maghraby et al [17] found that (78%) of the studied subjects were having poor social functioning.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Schizophrenia is a chronic psychotic condition affecting approximately 24,000,000 individuals worldwide and constitutes the majority of patients in psychiatric facilities of Egypt [13,14] . Social functioning is very impaired among schizophrenic patients and is repeatedly associated with poor adherence to medical treatment, poor prognosis, higher relapse rate, and increased risk of premature mortality [15,16] . A study conducted by Al-Maghraby et al [17] found that (78%) of the studied subjects were having poor social functioning.…”
Section: Significance Of the Studymentioning
confidence: 99%